The career experiences of football association coach educators: Lessons in micropolitical literacy and action - Allanson, A.; Potrac, P.; Nelson, L. (Qualitative Research in Sport, Exercise and Health, 2021)
Coach education has been the subject of increasing investigation in recent years. While such inquiry has provided important insights into coaches` engagements with various forms of coach education provision, coach educators` perspectives have remained curiously absent from the literature base. This study provides rich insights into the ways in which four Football Association (FA) coach educators interpreted their everyday workplace relationships with various significant others (e.g., their line managers, colleagues, and coach learners). In-depth, cyclic interviews were utilised to generate the data. The transcripts were iteratively analysed using symbolic interactionist and dramaturgical theorisations of social life. The analysis highlighted how the participants` interactions and identity management were influenced by their understandings of others` expectations of acceptable workplace performance, as well as their own career related aspirations. Here, the participants demonstrated a nuanced ability to `read` and `write` themselves into the micropolitical and uncertain terrain of coach education work. It is hoped that this study highlights the utility of symbolic interactionist and dramaturgical theories to the critical examination of coach education work and, relatedly, how such inquiry could be used to assist in the preparation and on-going professional development of coach educators.